(untitled) (Historia, 2021)
At the outbreak of the Second World War, the Union Defence Force (UDF) had to undergo a rapid transformation from an ageing peacetime defence force to one that could project its offensive power across the African subcontinent. The formation of the 1st South African Division during 1940 and the subsequent deployment of South African troops to the East African theatre as part of the East Africa Force, afforded the UDF the opportunity to test its military capabilities under operational conditions against the Italian threat in Abyssinia (now Ethiopia) and Italian Somaliland (Somalia). The Allied offensives in East Africa began with the successful attack on El Wak on 16 December 1940, in which some South African troops received their baptism of fire. The combat experience gained by the South African troops at El Wak proved paramount, because it was the first instance in which the UDF was able to gauge its fighting efficiency and hence evaluate concepts such as force design, doctrine, military innovation and the operational employment of troops, to name but a few. The Allied success at El Wak was the impetus needed for the beginning of offensive operations in the East African theatre before the arrival of the rainy season. Between January and April 1941, the East Africa Force launched a series of successful attacks across Abyssinia and Italian Somaliland, culminating in the capture of Addis Ababa and the penultimate battle of Amba Alagi. In a mere fifty-three days, Allied troops advanced more than 2 700 kilometres from the Kenyan frontier to Addis Ababa, occupying some 580 000 square kilometres and capturing more than 50 000 prisoners. At the time, it was described as a military record, with offensive operations carried out at a pace seldom surpassed in history. The South African troops played a vital role in securing the first campaign victory of the war, and often acted as the vanguard during offensive operations across the theatre.